THE INFLUENCE OF THE TRANSITION TO SMALLER NECESSARY NAVIGATION CHARACTERISTICS ON THE LIKELIHOOD OF A DISASTER DURING ZONAL NAVIGATION FOR DIFFERENT TYPES OF AIRCRAFT - Корчунов, Д. О. (Proceedings of National Aviation University (archive), 2021)
The influence of the transition to promising RNPs in zonal navigation for different types is considered aircraft in accordance with ICAO standards.